Kohleausstieg 2030 unter neuen Vorzeichen; The German coal phase-out in 2030 under current developments - Jonas Egerer; Veronika Grimm; Lukas M. Lang; Ulrike Pfefferer (Wirtschaftsdienst, 2022)
Der russische Angriff auf die Ukraine und die Abhängigkeit der deutschen Energiewirtschaft von russischem Gas führen aktuell zu einer sehr angespannten Versorgungssituation, die sich im kommenden Winter noch verschärfen könnte. Auch mittelfristig dürfte der Importpreis für Erdgas deutlich oberhalb der historischen Werte liegen, wenn Europa sich von Russland unabhängig aufstellt. Diese Entwicklungen erfordern eine Neubewertung der deutschen Energiepolitik, unter anderem für die Energiewende im Stromsektor. – – The Russian attack on Ukraine and the German energy industry's dependence on Russian gas are currently leading to a very tight supply situation, which could worsen in the coming winter. In the medium term, too, the import price for natural gas is likely to be significantly above historical levels as Europe becomes independent of Russian gas. These developments call for a reassessment of German energy policy, including for the energy transition in the power sector.
Keywords: J11; J32; H20; H32; 330; Energiepolitik; Energiewirtschaft; Deutschland